LEARNING GEOMETRY TRANSFORMATIONS USING BATIK MOTIFS: SYSTEMATIC LITERATURE REVIEW - Yufitri Yanto; Zulkardi; Ratu Ilma Indra Putri; Duano Sapta Nusantara (STKIP Andi Matappa, 2024)
This article describes the results of research on learning geometric transformations using batik motifs asteaching material for students. The research method chosen was the Systematic Literature Review (SLR)method, using the PRISMA protocol. The selection process followed the four stages of PRISMA:identification, screening, eligibility, and inclusion. The study involved documenting and reviewing sevenarticles related to geometric transformations using batik motifs. The findings indicate that the use of batikmotifs in teaching geometric transformations can positively impact students' learning.